A COMBINED ULTRASOUND AND CLINICAL SCORING MODEL FOR THE PREDICTION OF PERIPARTUM COMPLICATIONS IN PREGNANCIES COMPLICATED BY PLACENTA PREVIA - GOYAL, SHREEJI; SHARMA, SUJATA; SINGH, ARVINDER; KAUR, AMARJEET (Asian Journal of Pharmaceutical and Clinical Research, 2021)
Introduction: Patients with placenta previa are at an increased risk of uncontrolled hemorrhage. Various clinical and ultrasound parameters can predict the risk of bleeding in these patients. Hence, the objective of our study is to develop a combined ultrasound and clinical scoring model for the prediction of peripartum complications in pregnancies complicated by placenta previa. Methods: Fifty singleton pregnant women with placenta previa who underwent cesarean delivery in our hospital were included in the study. We collected clinical and ultrasound data prospectively, and the score was given to each parameter, and total score correlated with the occurrence of peripartum complications. Clinical parameters included age, parity, history of dilatation and evacuation, previous cesarean delivery, history of placenta previa, antepartum hemorrhage, and ultrasound parameters included type of previa, no. of lacunae in placenta, uteroplacental hypervascularity. The peripartum complications noted were the need for blood transfusion, uterine artery ligation, and cesarean hysterectomy. Results: According to the composite scoring done, uterine artery ligation was needed in more than 50% of patients at a score of 9–10. It increased to 100% as the score increased to ≥11. At a score of ≥12, hysterectomy was needed in around 75% of patients, and 100% of patients needed a blood transfusion. Univariate analysis using the Pearson Chi-square test was also done to know whether individual parameters and peripartum complications were significantly related that is p<0.05 with one another. Conclusion: The scoring system may serve to predict peripartum complications in pregnancies complicated by placenta previa.